2022
DOI: 10.3389/fpsyg.2022.876710
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Team Performance and Knowledge Hiding: Mediated by Interpersonal Mistrust

Abstract: Although scholars have acknowledged that knowledge hiding is negatively with team performance, none of the extant research has revealed the relationship between knowledge hiding and the performance of temporary teams. To fill this gap, we will explore whether and how knowledge hiding influences temporary team performance. Following a literature review, the correlation between knowledge hiding, interpersonal distrust, and temporary team performance is explored, and the theoretical model between variables is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Scholars have used psychological capital as a mediating variable in their models when examining the relationship between the role of abusive supervision, ethical leadership, and knowledge sharing, empirical results showed that psychological capital was positively related to knowledge sharing ( Agarwal and Anantatmula, 2021 ; Goswami and Agrawal, 2022 ); Zhu used psychological capital as a mediating variable when exploring the relationship between perceived overqualification and knowledge hiding behavior, and the results showed that psychological capital has a negative effect on knowledge hiding ( Zhu et al, 2022 ). By combing through the relevant literature, Dongling et al (2022) found that knowledge sharing has a positive impact on firm innovation performance, and the empirical results show that member knowledge sharing in the era of big data significantly impact the innovation performance of eSports industry knowledge alliances ( Yue et al, 2022 ); scholars have shown through their research that knowledge hiding as an independent or mediating variable has a negative effect on task performance ( Tian et al, 2022 ), team performance ( Miao et al, 2022 ), organizational performance ( Wen and Ma, 2021 ), and innovation performance ( Rong and Liu, 2021 ) of firms. In summary, psychological capital has a correlation with knowledge sharing and knowledge hiding, and at the same time, knowledge sharing, knowledge hiding and innovation performance also have a correlation, but the existing literature lacks an overall study of the above four variables, and the inner connection between the four needs to be explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have used psychological capital as a mediating variable in their models when examining the relationship between the role of abusive supervision, ethical leadership, and knowledge sharing, empirical results showed that psychological capital was positively related to knowledge sharing ( Agarwal and Anantatmula, 2021 ; Goswami and Agrawal, 2022 ); Zhu used psychological capital as a mediating variable when exploring the relationship between perceived overqualification and knowledge hiding behavior, and the results showed that psychological capital has a negative effect on knowledge hiding ( Zhu et al, 2022 ). By combing through the relevant literature, Dongling et al (2022) found that knowledge sharing has a positive impact on firm innovation performance, and the empirical results show that member knowledge sharing in the era of big data significantly impact the innovation performance of eSports industry knowledge alliances ( Yue et al, 2022 ); scholars have shown through their research that knowledge hiding as an independent or mediating variable has a negative effect on task performance ( Tian et al, 2022 ), team performance ( Miao et al, 2022 ), organizational performance ( Wen and Ma, 2021 ), and innovation performance ( Rong and Liu, 2021 ) of firms. In summary, psychological capital has a correlation with knowledge sharing and knowledge hiding, and at the same time, knowledge sharing, knowledge hiding and innovation performance also have a correlation, but the existing literature lacks an overall study of the above four variables, and the inner connection between the four needs to be explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…From the overall perspective of team management, the ability of a team to achieve creative results is primarily determined by the director’s traits ( Miao et al, 2022 ; Sørensen et al, 2022 ). In recent years, regulatory focus has gradually received attention in the field of leadership research as a new perspective in the field of organizational behavior.…”
Section: Introductionmentioning
confidence: 99%